The rise of women : the growing gender gap in education and what it means for American schools - DiPrete, Thomas A.; Buchmann, Claudia (Russell Sage Foundation, 2013)
While powerful gender inequalities remain in American society, women have made substantial gains and have largely surpassed men in one crucial arena: education. By the early twenty-first century, women have come to outperform men academically at all levels of school, and are more likely to obtain college degrees and enroll in graduate school. What accounts for this enormous reversal in the gender education gap? In this book, the authors provide a detailed and accessible account of women’s educational advantage and suggest strategies to improve schooling outcomes for both boys and girls.